Violência sexual contra crianças e adolescentes no Brasil: uma revisão sistemática da literatura - Antônio Carlos Miranda; Maria de Lourdes Mattos Barreto; Viviani Silva Lírio; Felippe Clemente (Ciências Sociais Unisinos)
We propose to conduct a systematic literature review of postgraduate research, which relevant information on the issue of sexual violence against children and adolescents in Brazil. After the selection of 46 researches, we identify the prevalence of research carried out in Public Institutions (IFES) located in the Northeast and Southeast regions. Regarding the profile of the victims, sexual violence against girls prevails, and the risk of violence increases as they approach adolescence (between 12 and 14 years old). It was quite clear that the theme should be understood from a multidisciplinary aspect, thus requiring articulation between the various social actors involved in the formulation of public policies aimed at protecting children and adolescents.